E-Commerce Penjualan Obat Herbal pada Toko PO.Propolis dan Herbal Center Medan - Pania, Sadri; Harahap, Muhammad Khoiruddin (Politeknik Ganesha Medan, 2020)
Abstract— Technology and information currently growing and advancing need to be balanced according to the needs of the current era, because the more complex the work carried out, it cannot be denied at any institution or other institution that requires technology that can help and improve the work. Likewise, the marketing of Herbal Products at PO.Propolis Herbal Center Medan, the current information system is still functioning semi-computerized. This research discusses and makes information systems that can help in sales at PO.Propolis Stores & Medan Herbal Centers which have been using manuals. And facilitate the work of employees in managing data. Complete marketing results data quickly and relatively quickly. The information system is designed using the PHP programming language with a MySQL database. Tests carried out using the Black Box test and White Box test. The results of the research have made E-Commerce which can help the information system that runs better